An Overview of Pricing Models for Using Cloud Services with analysis on Pay-Per-Use Model - Lowe, Devesh; Galhotra, Bhavna (International Journal of Engineering and Technology, 2018)
Emergence of Cloud computing in recent years has provided various options to end-users w.r.t. cloud services. Different end users have different requirements for cloud services such as IAAS, PAAS & SAAS, but these services can be availed using different pricing mechanisms such as PPU, PFR, leased based, subscription based and dynamic pricing based on factors such as initial cost, lease period, QoS, Age of resources and cost of maintenance. The authors work focusses on ‘pay-per-use’ model of cloud pricing by studying various aspects of this model and comparing the current pricing rates of leading cloud service provider. Through this paper, the authors try to analyse the pricing model used by provider by comparing similar pricing offered by competitors. Authors will also try to establish the fairness of pricing as basis for designing better model for such services. The idea of pay per use has emerged to counter the rampant software piracy, while capturing the marginal and heterogeneous users who have been often found to use pirated software, as the acquisition costs for perpetual usage are too high. The marginal usage does not justify the huge capital investment of perpetual license, thereby leading to software piracy. In this paper the authors have also discussed on the Pay per use SaaS model and how it is better than the perpetual licencing, Pay per use is primarily dependent upon certain market conditions, like higher potential for piracy, lower inconvenience costs, majority of marginal users, and strong cloud network presence. Whereas perpetual licensing is important for heavy users, a market having the above-mentioned conditions will always benefit the SaaS pay per use model. So while the developer finds advantages of increased authorized user network, lower costs of marketing, enhanced customer reliability, and lesser impact of piracy, the rewards for users are even greater as they get to use the licensed full & updated versions for a small fee, even for minor everyday usage without incurring the huge expenditure on acquisition.